2000
DOI: 10.1080/02688690050175265
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombin complex concentrate for oral anticoagulant reversal in neurosurgical emergencies

Abstract: The incidence of spontaneous intracranial haemorrhage has increased markedly in line with the increased use of oral anticoagulant agents. Recent guidelines for reversal of this acquired coagulation defect in an emergency have been established, but they are not adhered to in all centres. Our unit is referred between 20 and 60 patients per year (1994-1999) who are anticoagulated and require urgent neurosurgical intervention. In order to investigate this, we performed a prospective study using prothrombin complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…Several studies comparing the efficacy of PCCs with human plasma for emergency oral anticoagulant reversal have shown that PCCs provide more effective and more rapid correction of coagulopathy [44-47]. These findings, together with the improved safety profile of today's PCCs, suggest that PCCs should be considered preferable to FFP for emergency oral anticoagulant reversal.…”
Section: Comparing Pccs With Human Plasmamentioning
confidence: 99%
“…Several studies comparing the efficacy of PCCs with human plasma for emergency oral anticoagulant reversal have shown that PCCs provide more effective and more rapid correction of coagulopathy [44-47]. These findings, together with the improved safety profile of today's PCCs, suggest that PCCs should be considered preferable to FFP for emergency oral anticoagulant reversal.…”
Section: Comparing Pccs With Human Plasmamentioning
confidence: 99%
“…Similarly, in a prospective study 52 of 41 patients requiring rapid reversal of VKA-associated overanticoagulation, 28 of 29 patients treated with 4F PCC showed a complete correction of the INR within 15 minutes (mean INR of 1.3), while 0 of 12 patients treated with FFP corrected within this time frame (mean INR of 2.3). A number of other studies 15,24,49,50,5358 have confirmed the efficacy of PCCs in the rapid reversal of elevated INRs.…”
Section: Treatment Options For Reversal Of Overanticoagulationmentioning
confidence: 78%
“…Despite the increasing use of PCC, including activated PCC, there are no large RCTs to support its use other than in haemophilia [469-471] or for the rapid reversal of the effect of oral vitamin K antagonists [472-474]. In the setting of trauma patients treated with pre-injury warfarin, a retrospective analysis showed that the use of PCC resulted in a more rapid time to reversal of the INR [475-478].…”
Section: Resultsmentioning
confidence: 99%